Diffusion tensor imaging of the abdominal organs: Influence of oriented intravoxel flow compartments. (9th August 2019) - Phi van, Valerie; Reiner, Caecilia S.; Klarhoefer, Markus; Ciritsis, Alexander; Eberhardt, Christian; Wurnig, Moritz C.; Rossi, Cristina
Abstract : Water flow in partially oriented intravoxel compartments mimics an anisotropic fast‐diffusion regime, which contributes to the signal attenuation in diffusion‐weighted images. In the abdominal organs, this flow may reflect physiological fluid movements (eg, tubular urine flow in kidneys, or bile flow through the liver) and have a clinical relevance. This study investigated the influence of anisotropic intravoxel water flow on diffusion tensor imaging (DTI) of the abdominal organs. Diffusion‐weighted images were acquired in five healthy volunteers using an EPI sequence with diffusion preparation (TR/TE: 1000 ms/71 ms; b‐values: 0, 10, 20, 40, 70, 120, 250, 450, 700, 1000 s/mm 2 ; 12 noncollinear diffusion‐encoding directions). DTI of liver and kidneys was performed assuming (i) monoexponential decay of the diffusion‐weighted signal, and (ii) accounting for potential anisotropy of the fast‐diffusion compartments using a tensorial generalization of the IVIM model. Additionally, potential dependency of the metrics of the tensors from the anatomical location was evaluated. Significant differences in the metrics of the diffusion tensor (DT) were found in both liver and kidneys when comparing the two models. In both organs, the trace and the fractional anisotropy of the DT were significantly higher in the monoexponential model than when accounting for perfusion. The comparison of areas of the liver proximal to the hilum with distal regions and of renal cortex with the medulla also proved a location dependency of the size of the fast‐diffusion compartments. Pseudo‐diffusion correction in DTI enables the assessment of the solid parenchyma regardless of the organ perfusion or other pseudo‐diffusive fluid movements. This may have a clinical relevance in the assessment of parenchymal pathologies (eg, liver fibrosis). The fast pseudo‐diffusion components present a detectable anisotropy, which may reflect the hepatic microcirculation or other sources of mesoscopic fluid movement in the abdominal organs. Abstract : In the abdominal organs, water flow in partially oriented intravoxel compartments originated by physiological fluid movements (eg, tubular urine flow in the kidneys, or bile flow through the liver) can be quantified using a tensorial generalization of the IVIM model. Pseudo‐diffusion correction in DTI enables assessment of the solid parenchyma, regardless of the organ perfusion or other pseudo‐diffusive fluid movements.